Analysis of the Influence of Restaurant Taxes, Advertising Taxes and Regional Lovies on the Original Income of South - Eso Hernawan; Artedy Tanto (Komunitas Dosen Indonesia, 2019)
The aim of this research to obtain empirical evidence about the leverage, profitability and size of firm to tax aggressiveness. Population of this research is the audited financial statements in manufacturing company food and beverage sub-sector and cosmetic sub-sector and household goods listed in Indonesia Stock Exchange in 2014-2017. Determination of the sample was done by using purposive sampling with the number of samples of 11 companies over a period of 4 years of consecutive observations so that the total sample of 44. This research data using SPSS version 21 with descriptive statistical test, classical assumption test, multiple linear regression analysis, hypothesis test The results of the research that has been processed shows that the significant value of leverage that is proxied using DER is 0.275, the significant value of profitability proxyed using ROA is 0.001, and the significant value of firm size proxied using LN is 0,000. And from the results of research show that leverage does not have a significant effect on tax aggressiveness, while profitability and firm size have an effect on the aggressiveness of tax